Using a Mediator's Toolbox: Reducing Clinical Conflict by Learning to Reconceive the “Difficult” Patient or Family - Autumn Fiester; Shana Stites (MedEdPORTAL, 2023)
Introduction Given the prevalence of conflict between physicians and patients and families, it is crucial that trainees build the skills to manage clinical conflict. Mediators employ an approach that can be applied to clinical encounters to prevent conflicts from escalating. This workshop introduced trainees to techniques commonly used by mediators to manage disputes. Methods Medical students in a virtual workshop (cohort A) and clinical fellows in an in-person workshop (cohort B) were presented with a mediator's approach to interpreting patient and family behavior viewed as challenging. Trainees were introduced to two specific techniques designed to facilitate the resolution of clinical conflict. After an interactive large-group discussion of each method, small groups practiced applying the technique to a sample clinical case. Finally, participants completed an assessment of their perception of the workshop's effectiveness. Results In early 2022, 15 medical students (cohort A) participated in a virtual workshop and 10 clinical fellows (cohort B) participated in an in-person workshop on clinical conflict management. Eight medical students from cohort A completed the postworkshop assessment (response rate: 53%); six clinical fellows from cohort B completed the assessment (response rate: 60%). Cohort A gave the workshop an overall evaluation of 4.6 out of 5.0; cohort B gave the workshop an overall score of 4.7 out of 5.0. Discussion In both the virtual platform and the traditional in-person format, this workshop introduces a set of tools for navigating bedside conflicts with patients and their families that participants believed would better prepare them for such challenging interactions.